The concept of emancipation as political action - Zdravković, Lana (Filozofski vestnik, 2021)
The text attempts to rethink the concept of emancipation and how it is structured as political action, while describing its historical origins and how it is further understood by the three important political philosophers: Karl Marx, Hannah Arendt, and Jacques Ranciere. All three of them – specifically and with substantial differences – understand politics as a space for political action that leads to emancipation in the name of equality. In order to determine the historical origin of the concept in more detail, the argumentation of the text rely upon its elaboration within the school of “conceptual history”, which deals with the historical semantics of terms and sees the etymology of and the change in the meaning of terms as forming a crucial basis for a contemporary cultural, conceptual, and linguistic understanding, and afterwards it links this “pre-history” with Marx’s, Arendt’s, and Ranciere’s understanding of the concept of emancipation, and see how they differ and are related to each other, considering what theoretical conclusions about the concept of emancipation we can take from these relations. Particular interest is aimed at how the concept of emancipation is perceived today, who the subject of emancipation is, what the method and final goal of emancipation is, and, finally, how these understandings can help us in the present time when it seems that we need emancipation more than ever.
Keywords: človeška emancipacija; freedom; human emancipation; intelektualna emancipacija; intellectual emancipation; liberation; osvoboditev; political emancipation; politična emancipacija; revolucija; revolution; svoboda